IDENTITAS ISLAM DALAM KEBIJAKAN LUAR NEGERI INDONESIA TERHADAP PALESTINA, STUDI KASUS : PENYELENGGARAAN KONFERENSI TINGKAT TINGGI (KTT) LUAR BIASA KE-5 TAHUN 2016 ORGANISASI KERJASAMA ISLAM (OKI) DI JAKARTA - Atep Abdurofiq (Universitas Nasional, 2016)
The Government of the Republic of Indonesia hosted the 5th Extraordinary Summit Organisation of Islamic Cooperation (OIC) on Palestine and Al-Quds Al-Sharif in Jakarta on March 7, 2016. The event reflects the Islamic identity in Indonesia’s foreign policy. The event is analyzed by the constructivist perspective. In constructivist perspective, interests and State's behavior are influenced by the meaning States’s identity. The identity is the result of a State’s internal and external preference. Islamic identity embodied in Indonesia's interests to get recognition, economic interests and the protection of Indonesian Workers in Middle East Countries. Keywords: Identity, Interests, Foreign Policy